2015
DOI: 10.1371/journal.pone.0117208
|View full text |Cite
|
Sign up to set email alerts
|

Prion Pathogenesis in the Absence of NLRP3/ASC Inflammasomes

Abstract: The accumulation of the scrapie prion protein PrPSc, a misfolded conformer of the cellular prion protein PrPC, is a crucial feature of prion diseases. In the central nervous system, this process is accompanied by conspicuous microglia activation. The NLRP3 inflammasome is a multi-molecular complex which can sense heterogeneous pathogen-associated molecular patterns and culminates in the activation of caspase 1 and release of IL 1β. The NLRP3 inflammasome was reported to be essential for IL 1β release after in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 72 publications
2
30
0
Order By: Relevance
“…The microglial characteristics during the early stages of CNS prion disease are instead similar to the anti-inflammatory profile exhibited by macrophages following their engulfment of apoptotic cells [ 171 ]. This is consistent with data showing that CNS prion disease is unaltered in the steady state in mice lacking the NLRP3 inflammasome [ 172 ] (essential for release of IL-1β), NF-κB signalling [ 173 ] or MyD88 signalling [ 174 ]. Treatment of scrapie-affected sheep with the glucocorticoid dexamethasone during the clinical phase similarly had no effect on the development of neuropathology [ 175 ].…”
Section: Cns Prion Diseasesupporting
confidence: 91%
“…The microglial characteristics during the early stages of CNS prion disease are instead similar to the anti-inflammatory profile exhibited by macrophages following their engulfment of apoptotic cells [ 171 ]. This is consistent with data showing that CNS prion disease is unaltered in the steady state in mice lacking the NLRP3 inflammasome [ 172 ] (essential for release of IL-1β), NF-κB signalling [ 173 ] or MyD88 signalling [ 174 ]. Treatment of scrapie-affected sheep with the glucocorticoid dexamethasone during the clinical phase similarly had no effect on the development of neuropathology [ 175 ].…”
Section: Cns Prion Diseasesupporting
confidence: 91%
“…In a recently published work, Nuvolone et al (2014) demonstrated that NALP3 and ASC have limited role in prion pathogenesis in vivo model with RML6 strain. This might be due to strain dependent differences in prion infections.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the absence of NLRP3 or ASC did not significantly change levels of IL-1β in the brain at the terminal stage of the disease. Thus, based on existing data, NLRP3 and ASC do not play significant roles in prion pathogenesis (89).…”
Section: R E V I E W S E R I E S : G L I a A N D N E U R O D E G E N mentioning
confidence: 97%